Korea's Growth Experience and Long-Term Growth Model - Jeong, Hyeok (World Bank, Washington, DC, 2017)
This paper analyzes the Republic of Korea's rapid and sustained growth experience for the past six decades from the perspective of the neoclassical growth model (the workhorse model of the World Bank’s Long Term Growth Model (LTGM) project). Overall, the sources of Korea's growth were balanced among labor market and demographic factors, capital investment, human capital accumulation, and productivity growth. However, the main engine of growth evolved sequentially, e.g., labor and human capital factors in the 1960s, capital deepening in the 1970s, and then productivity growth for the following periods. The major sources of sustained growth over six decades were human capital accumulation and productivity growth rather than labor or capital investment. A counterfactual calibration of the model explains Korea's actual growth experience well, and shows why gaps between the model’s predictions and the data arise. This illustrates that an appropriate calibration of a simple neoclassical growth model provides useful lessons and tools for policy makers in developing countries in designing their national development strategies.